1990
DOI: 10.1021/bi00458a032
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of position 12 in a parathyroid hormone and parathyroid hormone-related protein: toward the design of highly potent antagonists

Abstract: Truncated N-terminal fragments of parathyroid hormone (PTH), [Tyr34]bovine PTH(7-34)NH2, and parathyroid hormone related protein (PTHrP), PTHrP(7-34)NH2, inhibit [Nle8,18,[125I]iodo-Tyr34]-bPTH(1-34)NH2 binding and PTH-stimulated adenylate cyclase in bone and kidney assays. However, the receptor interactions of these peptides are 2-3 orders of magnitude weaker than those of their agonist counterparts. To produce an antagonist with increased receptor-binding affinity but lacking agonist-like properties, structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…Deletion of residues 1–6 from the PTH(1–34) scaffold produced analogues that no longer activate signalling via the cAMP–PKA pathway, but instead, function as competitive antagonists of PTHR1-mediated cAMP signalling. 36 Further modification of the PTH(7–34) scaffold at residue position 12 produced an analogue, DTrp 12 -PTH(7–34), which in addition to competitively antagonizing cAMP signalling at PTHR1, 37 also acts as an inverse agonist and consequently reduces basal cAMP signalling at certain constitutively active PTHR1 variants. 38 Other PTH and PTHrP ligand analogues modified at residue position 1 have been developed that preferentially activate Gα S -cAMP signalling over Gα q -PLC-β signalling.…”
Section: Altered Signalling Of Pthr1 Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of residues 1–6 from the PTH(1–34) scaffold produced analogues that no longer activate signalling via the cAMP–PKA pathway, but instead, function as competitive antagonists of PTHR1-mediated cAMP signalling. 36 Further modification of the PTH(7–34) scaffold at residue position 12 produced an analogue, DTrp 12 -PTH(7–34), which in addition to competitively antagonizing cAMP signalling at PTHR1, 37 also acts as an inverse agonist and consequently reduces basal cAMP signalling at certain constitutively active PTHR1 variants. 38 Other PTH and PTHrP ligand analogues modified at residue position 1 have been developed that preferentially activate Gα S -cAMP signalling over Gα q -PLC-β signalling.…”
Section: Altered Signalling Of Pthr1 Ligandsmentioning
confidence: 99%
“…Analogues of DTrp 12 -PTH(7–34) can inhibit PTH-induced cAMP responses in cells 37 and calcaemic responses stimulated by exogenous PTH(1–34) in rats. 97 However, trials in patients with hypercalcaemia owing to primary hyperparathyroidism revealed a complete lack of efficacy for such a DTrp 12 -PTH(7–34) analogue in reversing hypercalcaemia.…”
Section: Pthr1 In Diseasementioning
confidence: 99%
“…A close analogue of 1 , containing Tyr at position 34 instead of Phe [PTH(1–34) numbering], has previously been tested in radiolabel binding assays. 12, 14 We included human PTH(1–34) (Figure 1a) as a positive control and point of comparison for peptides 1 and 2 . Bound radioactivity resulting from association of radiolabeled PTH(1–34) with PTHR1 is diminished in a dose-dependent fashion following addition of unlabeled PTH(1–34), α-peptide 1 , or α/β-peptide 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This part of the molecule has been identified as the core of a protein kinase C-activating domain of PTH and PTH-rP (7)(8)(9)(10)(11). The secondary structure of the two peptide hormones in this region is very similar (12), consisting of a helical motif. In PTH, the hydrophobic amino acids are placed on one side and the hydrophilic amino acids on the other side ( Fig.…”
mentioning
confidence: 99%